The Effect Of Cognitive Momentum On Sustainable Performance By Mediating Proactive Behavior - ALI, FIRAS MAHDI; MUHAMMED, DR. NISREEN JASSEM (The journal of contemporary issues in business and government, 2021)
The current research aims at verifying the impact of cognitive Momentum as an independent variable, in the sustainable performance of a responsive variable, by mediating proactive behavior in the headquarters of the General Automobile Company in Iraq, its divisions, staff, and units, in addition to diagnosing the level of interest of its leaders and subordinates in the research variables and their dimensions. Add to that, coming up with recommendations that contribute in promoting the applications of these three variables in the company being researched. and based on the researcher's devotion to diagnose the influence relationship between the variables, because of their effects on the company and its members on the one hand, and its reflection on society on the other hand. The descriptive exploratory approach was adopted in completing the current research chapters and topics, as the research community included the headquarters of the General Automobile Company, which consisted of (523) employees. The researcher targeted an intentional stratigraphic sample of (223) members, which included: (the company’s general manager, assistant general manager, department director, associate department manager, division manager, garage manager, unit official, employee). All done through adopting the questionnaire which contained (54) paragraphs, personal interviews, and field inspection to enhance the practical side, while the researcher used statistical programs (26.V SPSS, 25.V Amos), to analyze the primary data, with the adoption of descriptive and inferential statistical methods, such as: (the normal distribution test, Confirmatory and Exploratory Factor Analysis, Percentage, Arithmetic Mean, Standard Deviation, Relative Difference Coefficient, Materiality, Pearson Correlation Coefficient, Simple Linear Regression Coefficient, Multiple Regression Coefficient) to test his hypothesis. As for the most prominent results of the research, they were represented by the influence of cognitive Momentum on sustainable performance, directly and indirectly, with a reliability level of (0.937) of cognitive Momentum, (0.950) for sustainable performance, and (0.967) for proactive behavior.